Financial market contagion in Asian crisis / Zaizura Mohd Shah (Faculty of Business and Management, 2007)
This study tests for evidence of contagion between the financial markets of Malaysia, Singapore and Japan during crisis. For that purpose, this paper focus on three variables which are interest rate, exchange rate and stock price correlation to capture the impact of cross border contagion. The objective of this paper is to examine correlation of exchange rate, interest rates and stock price between Malaysia, Singapore and Japan. To analyze the correlation, this research use Pearson-product-moment correlation to regress the exchange rate, interest rate and stock price. The data taken will be on monthly basis for five years period from 1997 until 2001. The time series selected was based on during crisis and after crisis. Based on the method used, this study found that there was a correlation between Malaysia, Singapore and Japan. Singapore represent that the country have highest correlation between Malaysia and Singapore for exchange rate, interest rate and stock price.